Health Problems of the Elderly Population in Some Selected Urban Slums of Dhaka City - Farah, Shayela; Karim, Mohoshina; Khatun, UH Shahera (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Aging is universal and it is inescapable, beginning at birth, which should be regarded as a normal biological process leading to functional deterioration, vulnerability and ultimately culminating to extinction of life. Population ageing is becoming a major concern both in the developed and developing countries. Many health problems are known to increase with age and this demographic trend may lead to an increase in the absolute number of health conditions in this population. To identify health problems of elderly population and assess their socioeconomic condition. This descriptive cross sectional study was carried out over 531 elderly people selected purposively from some urban slums of Dhaka city during July to December, 2013. Each eligible participant was informed about the purpose and procedure of the study. Trained interviewers collected information by face to face interview using a pre-tested questionnaire having both structured and open ended questions. Majority 389 (73.3%) were from the age group of 60-69 years. The mean age of the respondents was found to be 65 years; (SD±7.048). Majority of them were male 68.7%, illiterate 78.8%, employed as small businessman 26% and belonged to joint family 75.0%. Their average monthly income was 4747.02 ± 2796.368 Taka. About 272(51.2%) respondents were dependent on other earning family members. A significantly higher proportion of women suffered from diabetes, hearing impairment, vertigo, joint pain, depression, while chest pain, chronic cough, difficulty in micturation, anxiety were observed more in elderly men. The study sheds new light which may help to provide adequate guideline for the senior citizens to overcome old age health problems. As there is a rapid increase in the number of elderly population, there is an urgent need to develop affordable and accessible health care services. J Bangladesh Coll Phys Surg 2015; 33(4): 202-206